Regulation of astrocyte activation by glycolipids drives chronic CNS inflammation - Mayo, Lior; Trauger, Sunia A; Blain, Manon; Nadeau, Meghan; Patel, Bonny; Alvarez, Jorge I; Mascanfroni, Ivan D; Yeste, Ada; Kivisäkk, Pia; Kallas, Keith; Ellezam, Benjamin; Bakshi, Rohit; et al. (Nature medicine, 2014)
In multiple sclerosis and experimental autoimmune encephalomyelitis, astrocytes produce lactosylceramide, a glycolipid that promotes astrocyte and microglial activation and immune cell infiltration into the CNS. Astrocytes have complex roles in health and disease, thus it is important to study the pathways that regulate their function. Here we report that lactosylceramide (LacCer) synthesized by β-1,4-galactosyltransferase 6 (B4GALT6) is upregulated in the central nervous system (CNS) of mice during chronic experimental autoimmune encephalomyelitis (EAE), a model of multiple sclerosis (MS). LacCer acts in an autocrine manner to control astrocyte transcriptional programs that promote neurodegeneration. In addition, LacCer in astrocytes controls the recruitment and activation of microglia and CNS-infiltrating monocytes in a non–cell autonomous manner by regulating production of the chemokine CCL2 and granulocyte-macrophage colony–stimulating factor (GM-CSF), respectively. We also detected high B4GALT6 gene expression and LacCer concentrations in CNS MS lesions. Inhibition of LacCer synthesis in mice suppressed local CNS innate immunity and neurodegeneration in EAE and interfered with the activation of human astrocytes in vitro . Thus, B4GALT6 regulates astrocyte activation and is a potential therapeutic target for MS and other neuroinflammatory disorders.